2000
DOI: 10.1007/s005400050006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human plasma cholinesterase and erythrocyte acetylcholinesterase by nondepolarizing neuromuscular blocking agents

Abstract: Both plasma ChE and erythrocyte AChE were inhibited by six nondepolarizing NMBAs, and the pattern of inhibition of both enzymes was of mixed type. The inhibitory potencies of pancuronium and vecuronium for plasma ChE were larger than that of neostigmine, whereas those of the six nondepolarizing NMBAs for erythrocyte AChE were markedly lower than that of neostigmine. The rank order of relative potency for plasma ChE was pancuronium > vecuronium > pipecuronium > alcuronium > d-tubocurarine > atracurium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
3
8
1
Order By: Relevance
“…*P < 0.05 compared to control (drug-free Krebs buffer); **P < 0.05 vs d-tubocurarine alone rinic activities do not contribute to their fades, because atropine alone (blocking presynaptic M1 and M2 receptors) [2] or the selective blockade of facilitatory M1 receptors by pirenzepine does not produce fade. On the other hand, cisatracurium exhibited anticholinesterase activities similar to those of pancuronium, as reported previously [9]. Therefore, the anticholinesterase activities of pancuronium and cisatracurium induced the activation of presynaptic inhibitory M2 receptors, as well as stimulatory M1 receptors, by acetylcholine in the synaptic cleft.…”
Section: Fig 2 Absence Of Effects On R (Left) Andsupporting
confidence: 73%
See 1 more Smart Citation
“…*P < 0.05 compared to control (drug-free Krebs buffer); **P < 0.05 vs d-tubocurarine alone rinic activities do not contribute to their fades, because atropine alone (blocking presynaptic M1 and M2 receptors) [2] or the selective blockade of facilitatory M1 receptors by pirenzepine does not produce fade. On the other hand, cisatracurium exhibited anticholinesterase activities similar to those of pancuronium, as reported previously [9]. Therefore, the anticholinesterase activities of pancuronium and cisatracurium induced the activation of presynaptic inhibitory M2 receptors, as well as stimulatory M1 receptors, by acetylcholine in the synaptic cleft.…”
Section: Fig 2 Absence Of Effects On R (Left) Andsupporting
confidence: 73%
“…Although data indicate a role of M2 receptors in the fade induced by d-tubocurarine, hexamethonium, or neostigmine, they do not explain whether the excitatory M1 receptors are involved in the fades produced by these agents. Furthermore, a comparative investigation has still to be undertaken to verify whether there is any involvement of presynaptic M1 and/or M2 receptors in the fades induced by other antinicotinic agents (pancuronium and cisatracurium), which also exhibit antimuscarinic (pancuronium and cisatracurium) and/or anticholinesterase (pancuronium) activities [9,10]. Because identifi cation of the mechanisms through which the different antinicotinic agents produce fade could be clinically useful for the management of neuromuscular transmission in curarized patients, the effects of 10 nM pirenzepine or 1.0 μM methoctramine (concentrations that selectively block M2 receptors) [11] on the fade induced by dtubocurarine and hexamethonium were investigated in phrenic nerve-diaphragm muscle preparations of rats and then compared with those induced by antinicotinic agents (pancuronium, cisatracurium) [10].…”
Section: Introductionmentioning
confidence: 99%
“…9 Under the present experimental conditions, D-tubocurarine-, pancuronium-and hexamethonium-induced fade was attenuated by blocking presynaptic inhibitory M 2 receptors with methoctramine and presynaptic inhibitory A 1 receptors with DPCPX. Although pancuronium may exhibit antimuscarinic activity at therapeutic doses (K d~0 .28 lmol/L), 8,26 the blockade of muscarinic activity by this drug does not appear to have contributed to the fade observed in the present study because administration of the non-selective antimuscarinic drug atropine alone 27 and selective blockade of presynaptic M 1 and M 2 receptors did not produce a fade of nerveevoked muscle contractions. 15 Methoctramine and DPCPX enhanced rather than attenuated fade induced by cisatracurium when the phrenic nerve was stimulated with high-frequency trains (50 Hz for 10 s), but they consistently attenuated cisatracuriuminduced TOF fade triggered at 2 Hz nerve stimulation.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition, antimuscarinic and anticholinesterase properties may be observed when compounds such as pancuronium and cisatracurium, respectively, are applied at concentrations currently used in clinical practice. 8,9 Recent findings from our group 10 demonstrated that muscle paralysis using the muscle-type nicotinic irreversible antagonist a-bungarotoxin significantly decreased (by > 90%) nerve-evoked adenosine outflow via equilibrative nucleoside transporters without substantially affecting (~15%) the release of ATP from stimulated motor nerve terminals. Blockade of inhibitory M 2 autoreceptors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Antagonism of fade induced by hexamethonium or d ‐tubocurarine has been achieved by using the M 2 receptor antagonist methoctramine, 10 but such antagonism is not apparent when the preparation is treated with the M 1 receptor antagonist pirenzepine, demonstrating the distinct contribution of inhibitory presynaptic M 2 receptors in hexamethonium‐ and d ‐tubocurarine‐induced fade 10 . Presynaptic muscarinic (M 1 , M 2 ) and adenosine (A 1 ) receptors have been shown recently to participate in fade induced by antinicotinic agents that exhibit anticholinesterase activity (pancuronium, cisatracurium, vecuronium), 10–13 but the possible involvement of presynaptic A 2A receptors in the fade produced by these agents remains unknown. Activation of presynaptic A 2A receptors by CGS 21680C, a selective A 2A receptor agonist, increases the release of ACh from motor nerve terminals when rat neuromuscular preparations are stimulated indirectly at tetanizing frequencies 14 .…”
Section: Introductionmentioning
confidence: 99%